No longer alone - Lottie Sällström Randsalu; Kjerstin Stigmar (Scandinavian Journal of Primary Health Care)
Background and Purpose Absence from work due to illness is common in many western countries and has many negative consequences for both the individual and society. Since 2020 Swedish healthcare regions are required to provide resources to coordinate the rehabilitation process, a complex system involving medical as well as work-related parties, where both the physician and the rehabilitation coordinator play a central role. The aim of this study was to describe how primary care physicians experience the role of and the collaboration with a rehabilitation coordinatorMaterials and methods We used a qualitative design doing semi-structured interviews with primary care physicians (n= 9) in the Skåne healthcare region. The interviews were recorded, transcribed and analyzed using qualitative content analysis.Results One main category “An external and internal connecting point that has improved the sick-listing and rehabilitation process”, and four subcategories: “Provides relief for the individual physician”; “Offers practical support at the clinic”; “Gives increased sense of security for the patients” and “Sufficiently trained, with potential to take further responsibility”, were determined.Conclusions The study shows that primary care physicians experienced benefits from a close collaboration with a rehabilitation coordinator, feeling less lonely. The rehabilitation coordinator is often regarded as having a central role in insurance medicine related tasks, but an even more active role is desired.